A lion with wings a narrative-critical approach to Mark's Gospel - Smith, Stephen H. (Sheffield, UK Sheffield Academic, 1996)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Mark -- criticism, interpretation, etc